2001
DOI: 10.1017/s1041610201007463
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Improvement in Health-Related Quality of Life Among Elderly Patients With Depression

Abstract: Background: Depression is the most prevalent disabling psychiatric syndrome of aging and may lead to important decrements in the elderly depressed patient's health-related quality of life (HRQL). The goal of this study was to determine whether severity of chronic illness at admission, severity of depressive symptoms at admission, or living alone before admission was associated with lack of improvement in HRQL at 3 months postdischarge among elderly depressed inpatients. Methods: Subjects were 100 consecutive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
44
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 16 publications
(19 reference statements)
12
44
0
3
Order By: Relevance
“…In all, 45 studies reported that they excluded individuals with cognitive impairment or a diagnosis of dementia, of which 30 were cross-sectional studies (58.8%) [11,12,17,19,24,30,31,32,33,37,58,59,60,62,63,64,65,66,69,72,73,75,76,77,78,88,89,90,91,92] and 15 were longitudinal studies (68.2%) [2,3,4,8,10,18,20,21,25,26,34,45,46,48,49]. Cognitive function was equally assessed in clinical studies (n = 11) and in community-based studies (n = 12).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In all, 45 studies reported that they excluded individuals with cognitive impairment or a diagnosis of dementia, of which 30 were cross-sectional studies (58.8%) [11,12,17,19,24,30,31,32,33,37,58,59,60,62,63,64,65,66,69,72,73,75,76,77,78,88,89,90,91,92] and 15 were longitudinal studies (68.2%) [2,3,4,8,10,18,20,21,25,26,34,45,46,48,49]. Cognitive function was equally assessed in clinical studies (n = 11) and in community-based studies (n = 12).…”
Section: Resultsmentioning
confidence: 99%
“…Generally, most of the generic HQOL domains were affected in a negative way by a depressive disorder or a severe degree of depressive symptoms, except for physical functioning (role limitations due to physical health) and in the mental domain (emotional, psychological functioning) [3,10,21,25,45,82]. Two studies found that general health and vitality (and energy level) were not affected by depression [2,21] while spiritual, body pain, and satisfaction with living arrangements domains were not affected by depression in 1 study each [2,25,45].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher FTND scores were associated with a lower probability of a quit attempt, supporting the conclusion that higher levels of nicotine addiction hinder attempts at smoking cessation. The only factor significantly associated with sustained smoking cessation was a positive screening result, suggesting that lung cancer screening using recently published guidelines [48] could represent a unique opportunity to counsel patients about smoking cessation. This is in keeping with previously published studies examining the relationship of CT screening and screening results with smoking behavior [48][49][50].…”
Section: Discussionmentioning
confidence: 99%